Studi Etnobotani Dioscorea spp. (Dioscoreaceae) dan Kearifan Budaya Lokal Masyarakat di Sekitar Hutan Wonosadi Gunung Kidul Yogyakarta - Purnomo, Purnomo; Daryono, Budi Setiadi; Rugayah, Rugayah; Sumardi, Issirep (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Dioscorea spp. were cultivated as alternative food in the garden and yard on dry season, and it’s planted by peoples in the villages. The objectives of the research are to identify the species, the tuber use, and the local wisdom to support the conservation of Dioscorea around Wonosadi forest. Samples and data collection was conducted in 15 villages around Wonosadi forest. Interview survey was done on peoples who are cultivate yam species (Dioscorea spp.) in their garden. Research were emphasized to tuber characteristic, traditional uses, and local wisdom to supporting yam conservation. Data was analyzed descriptively to illustrate the kind of local usage and local wisdom of connect with Dioscorea spp. The results showed that there were found species of gembili (D. esculenta (Lour.) Burk.), uwi (D. alata L.), and gadung (D. hispida dennst.) as cultivated plants, and tomboreso (D. pentaphylla L.), gembolo (D. bulbifera L.), and jebubuk (D. numularia Lamk.) as wild species in the forest. Tuber is raw material for many kind of food based on carbohydrate content. Gadung were used as fickle food with high diversification and insecticide for rice and corn. Peoples more consume gembili and uwi than gembolo and others species as rice substitute at dry season. The local wisdom were indicated that peoples still consume gembili and uwi as rice substitute, while tuber also used as sesaji in traditional concept jajan pasar or tukon pasar, and tuber of uwi was used as diet for diabetes complaint, and row material of uwi ungu tuber was used effectively for diarrhea complaint in the villages.